Zeolitic Immidazole Framework-8 Synthesis with Hydrothermal and Addition of Tin Metal Ions - Fajri*, Rahmatul; Jofrishal, Jofrishal; Muslimah, Muslimah; Amri, Yulida; Hatijah, Hatijah; Permana, Dian; Tan, Siow-Ping (Jurnal IPA & Pembelajaran IPA, 2024)
This research is intended to synthesize Sn-ZIF-8 with an environmentally friendly hydrothermal method by exploring the potential of the utilization of aqueous solvents as the main solvent. Sn-ZIF-8 material has been successfully synthesized with water solvent at room temperature and has been characterized using XRD, FTIR, and SEM instrumentation to determine the extent of synthesis success. In this study, the use of Sn doping varied from 5, 10, and 15%, while MeIM, NH4OH, and water precursors were kept constant. Instrumentation observations showed the XRD patterns of Sn-ZIF-8 compounds for percentages of 5, 10, and 15% of Sn2+ displayed specific peaks of ZIF-8 at 2 = 7.24, 10.28, 12.62, 16.34, and 17.92. Meanwhile, the FTIR spectra of all synthesized solids presented the same functional group absorption peaks as the simulated ZIF-8 solids. SEM observation revealed a regular crystal shape of Sn-ZIF-8 without any contaminant on its surface. The characterization results show no change in the basic structure and the addition of other structures from ZIF-8. The implication of this finding can be utilized as a reference source for synthesizing inorganic materials using eco-friendly stages without affecting the synthesized product